Civil rights sit-ins - Harris, Duchess (Harris, Duchess. Protest movements., 2018)
Examines the powerful history of civil rights sit-in protests beginning with the Greensboro Four and their peaceful protest against racial inequality that sparked a movement. Includes text-related questions, a glossary, resources for further information, and archival photographs.